Expanding the Scope of Music Theory: Artistic Research in Music Performance - Mine Doğantan-Dack (Zeitschrift der Gesellschaft für Musiktheorie)
Artistic Research is a contemporary phenomenon that broadly refers to rigorous and systematic research undertaken in academic contexts by arts practitioners on their own creative processes and artistic products. As a field in continual emergence, evolution, and expansion, artistic research encourages a self-reflexive approach towards its own methods and outcomes. While artistic research in music performance is by now a well-established area, its connections with the discipline of music theory have so far not been explored in any significant detail. This article aims to take some initial steps towards investigating the relationships between these two ways of researching and knowing music. The discussion emphasizes points of tension as well as agreement, and promotes a view of artistic research in music performance as providing a robust broadening and bolstering of contemporary music theoretical activity.